IMPLEMENTASI CLOUD COMPUTING BERBASIS GOOGLE CLOUD UNTUK MENINGKATKAN KEBERLANJUTAN BISNIS DENGAN METODE AGILE - Muhammad Prasetyo; Raisa Humaida; safitri, safitri; Fenny Purwani (Journal of Scientech Research and Development, 2024)
This article discusses the use of Cloud Computing technology in supporting business sustainability through an Agile approach and a literature review. Cloud Computing offers flexibility, scalability, and cost efficiency that play a role in increasing business competitiveness. This study focuses on the Google Cloud platform, specifically related to the process of deployment, provisioning, and management of data infrastructure using Google Cloud SQL. The results of the study indicate that the implementation of Cloud Computing can improve operational efficiency and flexibility of companies, allowing them to respond quickly to market changes. This article also reveals the challenges faced, such as data security risks and dependence on internet connectivity. The Agile approach allows for more adaptive and iterative implementation, supporting changing business needs throughout the development process.